William J. Baroody papers - Baroody, William J., 1916-1980.
Correspondence, writings, speeches, reports, minutes of meetings, financial papers, biographical material, family papers, and other papers relating chiefly to Baroody's work as an executive of the American Enterprise Institute for Public Policy Research. Subjects include national and international issues such as commerce, economics, energy, health insurance, social security, and the influence of the broadcast media. Also documents Baroody's efforts to facilitate the immigration of family members and friends to the U.S. from the Middle East. Correspondents include Henry T. Bodman, Gerald R. Ford, Barry M. Goldwater, Robert A. Hornby, Carl N. Jacobs, Melvin R. Laird, A.D. Marshall, Paul Winston McCracken, William L. McGrath, G. Warren Nutter, Robert J. Pranger, Strom Thurmond, and Murray L. Weidenbaum.
Organization executive.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bodman, Henry T. -- 1906-1987 -- Correspondence; Ford, Gerald R., -- 1913-2006 -- Correspondence; Goldwater, Barry M. -- 1909-1998 -- Correspondence; Hornby, Robert A. -- 1900- -- Correspondence; Jacobs, Carl N. -- 1895- -- Correspondence; Laird, Melvin R. -- Correspondence; Marshall, A. D. -- 1901- -- Correspondence; McCracken, Paul W. -- 1915-2012 -- Correspondence; McGrath, William L. -- 1894- -- Correspondence; Nutter, G. Warren -- Correspondence; Pranger, Robert J. -- Correspondence; Thurmond, Strom, -- 1902-2003 -- Correspondence; Weidenbaum, Murray L. -- Correspondence; American Enterprise Institute for Public Policy Research; Commerce; Economics; Energy policy; Health insurance; Mass media -- Influence; Political planning; Social security; Middle East -- Emigration and immigration; United States -- Emigration and immigration; Executives